Future pharmacy practitioners' insights towards integration of artificial intelligence in healthcare education: Preliminary findings from Karachi, Pakistan. - Tahmina Maqbool; Humera Ishaq; Sadia Shakeel; Ayeshah Zaib Un Nisa; Hina Rehman; Shadab Kashif; Halima Sadia; Safila Naveed; Nazish Mumtaz; Sidra Siddiqui; Shazia Jamshed (PLoS ONE)
In an evolutionary era of medical education, "Artificial intelligence" (AI) is applied to replicate human intellect, encompassing abilities, logical reasoning and effective problem-solving skills. Previous research has explored the attitude of medical and dental students, toward the assimilation of AI in medicine; however, a significant gap exists in appraising the understanding and concerns of pharmacy students. Therefore, the current study was designed to explore undergraduate pharmacy students' perceptions of integrating AI into education and practice. Methods A cross-sectional study was conducted among final-year pharmacy students from different public and private sector universities in Karachi. The sample size on 60% anticipated response rate and 99% CI was calculated to be 390. Data was collected after acquiring ethical approval using convenient sampling. Frequency and percentage of the socio-demographic features were analyzed and then goodness of fit and Pearson's chi-squared test of correlation was applied. Results were considered significant when p < 0.05. Results The overall response rate of the study was 67%. More than 80% of the respondents were female. The students 35% (n = 202) strongly agreed and 59% (n = 334) agreed that AI plays an important role in healthcare, (χ2 = 505.6, p < 0.001). Around 79% (n = 453, χ2 = 384.3, p < 0.001) of students agreed on the replacement of patient care specialties with AI in the future, whereas 495 students (87%, χ2 = 682.3, p < 0.001) stated that they possess a strong comprehension of the fundamental principles governing the operation of AI. More than 80% of the students were comfortable in using AI terminologies (n = 475, χ2 = 598, p < 0.001) and 93% (n = 529, χ2 = 290, p < 0.001) were sure that AI inclusion in pharmacy education will develop a positive influence into the pharmacy curriculum (95%, n = 549, χ2 = 566.9, p < 0.001). A high and positive correlation was observed between the perception and willingness of students to adopt the AI changes in teaching undergraduate students (ρ = 0.491, p < 0.001). Furthermore, the outcomes showed students at private-sector universities stood out in computer literacy compared to public-sector universities (χ2 = 6.546, p < 0.05). Conclusion The current outcomes revealed the higher willingness of pharmacy students towards AI-infused learning. They understood the prerequisite of having both formal and informal learning experiences on the clinical application, technological constraints, and ethical considerations of the AI tools to be successful in this endeavor. The policymakers must take action to ensure that future pharmacists have a strong foundation of AI literacy and take initiatives to foster the interests and abilities of imminent pharmacists who will spearhead innovation in the field.